New grain fumigant - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Australian scientists have found that carbonyl sulphide, known to science for many years, has the potential to replace methyl bromide as a grain and soil fumigant (see Spore 47 p10). Although methyl bromide is the cheapest and easiest fumigant to...